2014
DOI: 10.1002/jbm.b.33170
|View full text |Cite
|
Sign up to set email alerts
|

In vivoimplantation of porous titanium alloy implants coated with magnesium-doped octacalcium phosphate and hydroxyapatite thin films using pulsed laser depostion

Abstract: The use of porous titanium-based implant materials for bone contact has been gaining ground in recent years. Selective laser melting (SLM) is a rapid prototyping method by which porous implants with highly defined external dimensions and internal architecture can be produced. The coating of porous implants produced by SLM with ceramic layers based on calcium phosphate (CaP) remains relatively unexplored, as does the doping of such coatings with magnesium (Mg) to promote bone formation. In this study, Mg-doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 42 publications
0
52
0
2
Order By: Relevance
“…These findings can be explained by considering a weak adhesion and/or minor coverage of the osteoblast cells on the Ti6Al4V alloys (see below). Thus, it can be assumed that there is a poor interaction between the extracellular matrix excretion (mainly type I collagen) and the TiO 2 ; likely due to its adsorption (via oxygen) through oxygen vacancies, as has been reported in the literature [16,26,31,53]. Regarding the R extra values, a slight increase is seen at 1 day for Ti6Al4V as received, Ti6Al4V 800 and Ti6Al4V 1050 alloys, followed by its decrease after 7 days of immersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings can be explained by considering a weak adhesion and/or minor coverage of the osteoblast cells on the Ti6Al4V alloys (see below). Thus, it can be assumed that there is a poor interaction between the extracellular matrix excretion (mainly type I collagen) and the TiO 2 ; likely due to its adsorption (via oxygen) through oxygen vacancies, as has been reported in the literature [16,26,31,53]. Regarding the R extra values, a slight increase is seen at 1 day for Ti6Al4V as received, Ti6Al4V 800 and Ti6Al4V 1050 alloys, followed by its decrease after 7 days of immersion.…”
Section: Resultsmentioning
confidence: 99%
“…These include mechanical, chemical, physical, thermal and heat treatments [19,20], thermomechanical [21] and deep cryogenic treatments [22], coatings [23,24,25], alkali-plus-heat [26], ion implantation [27,28,29], plasma spray [30], laser metal deposition (LMD) [31], selective laser melting and laser remelting (SLM) [32]. Heat treatments, in particular, may cause changes in the microstructure of the material depending on both temperature and cooling velocity, as well as on aging and alloy elements.…”
Section: Introductionmentioning
confidence: 99%
“…AM production and implantation of basic personalised implants based on XCT data are now commonplace, and reflecting this, a wide array of studies involving implantation have been published over the past year as the technology has become better understood [106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Clinical usage of metallic implants produced by AM in particular is now becoming common, specifically in maxillofacial and orthopaedic applications, though a number of issues remain preventing further adoption.…”
Section: Use For Implants (Stand-alone)mentioning
confidence: 99%
“…Selective laser melting (SLM) is a potential method to prepare homogeneous composites due to the rapid melting and solidifying process, which is able to limit the movement of the unmelted phase in the melt pool [15,16,17]. Wei et al [18] prepared stainless-steel/nano-hydroxyapatite composites by SLM and found that the decrease of solidification time could restrict the HA aggregation.…”
Section: Introductionmentioning
confidence: 99%